Landscape Theories A Brief Introduction - Kühne, Olaf.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2019)
In the past decades, the discussion about theoretical approaches to the topic of 'landscape' has increased. This book presents the currently discussed theoretical approaches to landscape and shows its potentials and limits. The theoretical approaches are discussed on the basis of current questions, such as socialisation and the hybridisation of landscape, and combined with empirical results. This is followed by a discussion of the landscape policy operationalisation of theoretical considerations and empirical findings. Contents • Currently Discussed Theoretical Perspectives On Landscape • Aesthetic Approaches to Landscape • The Differentiated Socialization of Landscape • Power and Landscape: From Political Worldviews and Critical Landscape Research • Current Issues in Social Science Landscape Research: Theoretical Classifications Audience Geographers, sociologists, landscape architects, landscape planners, regional planners, ethnologists, archeologists Author Dr. Dr. Olaf Kühne studied geography, modern history, economics and geology at Saarland University and received his doctorate degrees in geography and sociology from Saarland University and Hagen University. Habilitation from Mainz University. After working in various Saarland state authorities and at Saarland University, he was Professor of Rural Development/Regional Management at Weihenstephan-Triesdorf University of Applied Sciences and Associate Professor of Geography at Saarland University in Saarbrücken between 2013 and 2016. Since October 2016, he has been a professor of urban and regional development at the Eberhard Karls University of Tübingen.
Introductory Remarks -- Currently Discussed Theoretical Perspectives On Landscape -- Aesthetic Approaches to Landscape -- The Differentiated Socialization of Landscape -- Power and Landscape: From Political Worldviews and Critical Landscape Research -- Current Issues in Social Science Landscape Research: Theoretical Classifications -- Conclusion.
Keywords: Human geography; Sociology; Human Geography; Sociological Theory